A civil szervezetek program- és jogalkotásban való részvételének egyes kérdései Magyarországon - Rixer, Ádám (Debreceni Jogi Műhely, 2013)
Among the tools of including the concerned elements of society into the decision making processes the government operating since 2010 rather prefers the non-legal ones (i.e. those which do not constitute direct obligations for the government); rather solutions outside of the legal system are put into focus. Therefore the so-called national consultation, which – among others, such as sectoral, professional and other negotiating forums – introduced in Hungary a previously unknown political technique: within two years – in ordinary mail – each citizen received two surveys with possible answers to choose from, furthermore, – as a method not really used before in Hungary – an information booklet was sent to all citizens with the right to vote which presented the newest pieces of legislation.Looking beyond political slogans and pathetic forms it may be well observed that the government expects from the method of crowdsourcing – which may be considered traditional in other countries – as well as from different online consultations and the introduction of new means (surfaces) of information the establishment and deepening of discussion (cooperation) with society. Among the new means of information we shall mention that the government of Hungary created its websites civil.kormany.hu and kozhasznusag.kormany.hu related to the civil sector (in broader sense about legislation related to the civil sector). The websites – according to the intentions of the government– are part of the process of changing the attitude aimed at with the new act on the civil sector (Act CLXXV of 2011 on right of association, non-profit status, operation and support of NGOs), through which the government wishes to establish transparent connections with the civil sector.In Article 7 of the new Act CXXX of 2010 on legislation the two basic form of social compromise are described, general negotiation and direct negotiation. The former one provides opportunity for sharing opinion on the website of the organisation publishing concepts, drafts (in a way which obliges the organisation which asks for the opinion, e.g. through confirmation obligation or through preparing summaries on the merits), while the latter one allows the concerned minister to directly request persons and organisations to give opinion. A specific form of direct negotiation – creating obligations on the side of the minister – is the institution of strategic partnership, the framework of which is settled in a thorough agreement. One material weakness of the regulation, however, is that Article 13 paragraph (2) of the act only lists in an exemplary way those with whom such partnership may be concluded, by mentioning forms of organisations (e.g. church, trade union, civil organisation).